Case Study Of Padiberas Nasional Berhad (Bernas) - Tey, Lian Seng (2006)
This paper is going to examine BERNAS's historical approach to strategic alliances, followed by an internal and external analysis. Finally, the case for continuing or not the strategic alliance strategy will be discussed.